Microsoft Research at TREC 2009: Web and Relevance Feedback Tracks - Craswell, Nick; Fetterly, Dennis; Najork, Marc; Robertson, Stephen; Yilmaz, Emine (Proc. of the 18th Text Retrieval Conference (TREC), 2009)
We took part in theWeb and Relevance Feedback tracks, using the ClueWeb09 corpus. To process the corpus, we developed a parallel processing pipeline which avoids the generation of an inverted file. We describe the components of the parallel architecture and the pipeline and how we ran the TREC experiments, and we present effectiveness results.